2013
DOI: 10.5334/pb-53-1-93
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch Language Version of the Toronto Structured Interview for Alexithymia: Reliability, Factor Structure and Concurrent Validity

Abstract: The aim of this study was to evaluate the psychometric properties of the Dutch version of the Toronto Structured Interview for Alexithymia (TSIA) in a clinical sample. The TSIA and the 20-item Toronto Alexithymia Scale (TAS-20) were administered to 85 psychiatric inpatients and to 76 medical outpatients with the symptom of tinnitus. Both internal and inter-rater reliability were acceptable. Confirmatory factor analyses supported the hierarchical, 4-factor structure with 4 lower-order factors nested within 2 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 61 publications
3
19
2
Order By: Relevance
“…The correlation of r ¼.45 between self-report (TAS-20) and observer-rated (TSIA) measure of alexithymia in the current study is comparable with correlations found in other studies in which TAS-20 and TSIA have been administered. Bagby et al (2006), for example, reported a correlation of r¼ .36 in normal participants, whereas correlation coefficients of r ¼.34 (Inslegers et al, 2013), r ¼ .49 , or r ¼47 (Meganck et al, 2011) have been observed in patient samples. Caretti et al (2011) reported a correlation of r ¼.44 in a mixed sample of patients and healthy controls.…”
Section: Assessment Of Alexithymiamentioning
confidence: 85%
“…The correlation of r ¼.45 between self-report (TAS-20) and observer-rated (TSIA) measure of alexithymia in the current study is comparable with correlations found in other studies in which TAS-20 and TSIA have been administered. Bagby et al (2006), for example, reported a correlation of r¼ .36 in normal participants, whereas correlation coefficients of r ¼.34 (Inslegers et al, 2013), r ¼ .49 , or r ¼47 (Meganck et al, 2011) have been observed in patient samples. Caretti et al (2011) reported a correlation of r ¼.44 in a mixed sample of patients and healthy controls.…”
Section: Assessment Of Alexithymiamentioning
confidence: 85%
“…The Dutchspeaking group consisted of 85 psychiatric inpatients with a mood and/or anxiety disorder (32 men, 53 women; mean age¼39.92 years, S.D. ¼12.26) and 76 medical outpatients suffering from chronic tinnitus (48 men, 28 women; mean age¼47.82 years, S. D.¼13.42) recruited from several hospitals in the Dutch-speaking region of Belgium (for further details see Inslegers et al, 2013). The Italian-speaking group consisted of 62 psychiatric outpatients with a generalized anxiety disorder, dysthymia, or eating disorder (21 men, 41 women; mean age¼ 31.77 years, S.D.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…For this purpose, Bagby et al (2006) developed the Toronto Structured Interview for Alexithymia (TSIA) as an interview-based method for measuring the construct that may be used in conjunction with self-report or performance-based measures. The TSIA has been translated into Dutch, German, and Italian languages, and reliability, factorial validity, and concurrent validity of the measure have been demonstrated across clinical and nonclinical samples (Bagby et al, 2006;Grabe et al, 2009;Caretti et al, 2011;Inslegers et al, 2013). Notwithstanding cross-validation of the instrument and the use of back-translation procedures in developing the Dutch, German, and Italian translations of the TSIA, as noted by Ellis (1989), these steps are not sufficient to establish the property of measurement equivalence of any psychological or psychiatric test.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, the 24-item Toronto Structured Interview for Alexithymia [TSIA;24] was used to assess alexithymia. The TSIA is a reliable structured interviewbased method that, as an external rated device, prevents the bound of a self-evaluative approach as for example, do the dominant measures for assessing alexithymia [25,26]. This instrument has been recently proved to have no stable connection to self-reported negative affect [27] and, an additional strength of the TSIA, is to introduce items for detecting the lack of imaginative and fantasy aspects of the alexithymia construct [28,29].…”
Section: Introductionmentioning
confidence: 99%